The toxicity of different selenium forms and compounds – Review - Garousi, Farzaneh (Acta Agraria Debreceniensis, 2015)
Selenium (Se) is an unusual metalloid of considerable interest from both a toxicological and a nutritional perspective, with a very narrow safe range of intake. Although there are many reports about its detoxification properties, toxicity aspects of it have also been tracked for several decades. Lots of studies demonstrated that low Se is an efficacious avail whereas high Se can induce toxicity and the significant toxicity of selenium emphasizes the need to assess the health risk of various selenocompounds as nutritional supplements. The toxicity of different forms and compounds of selenium is also summarized in this review.